EVALUASI LAYANAN INTERNET BANKING BANK RAKYAT INDONESIA TERHADAP ASPEK USABILITY - Anggie Ariawan Dewa Putra; Wing Wahyu Winarno; Hanif Al Fatta (Universitas Janabadra, 2018)
The increasing need of modern society towards the internet resulted in banks trying to bring internet banking services in accordance with the wishes of the community to compete. The need for easy access, and user satisfaction is very important to note. In the context of website usability, the science of human computer interaction is required to be able to present a good website and in accordance with the needs of its users. This research is focused on evaluating usability of user interface of internet banking service of Bank Rakyat Indonesia using usability standard issued by ISO that usability website can be described as the level where product can be used by certain user to achieve its goal more effectively, efficiently and satisfactorily in scope Users. Then the usability techniques used in this research are think-aloud, performance measurement, and quistionaires to be able to cover the weaknesses of each technique. The results of the study using three usability techniques show the internet banking website BRI has fulfilled the needs of users will be effectiveness but still experience usability problems on efficiency and user satisfaction so that the improvement to cover the shortfall. The result of improved user interface shows a significant increase in usability points that become the weakness of the website. Keywords: Usability, User Interface, BRI, Think-Aloud, Perfomance-Measurement, Questionaires.